Narrativa audiovisual e performatividades de gênero : um estudo sobre a série Anne com E, da Netflix - Yasmine Feital Calçado Barbosa (2023)
This research analyzed the way in which the audiovisual narrative of the series Anne with E articulates gender performativities. To this end, we build on Judith Butler's theory of gender as performative (2021), reinforcing the linguistic and binary aspects that make up the discussion, and proposing a communicational look at gender. Such elements proved to be fundamental in the construction of the series. We also build on the studies of gender, media and audiovisual culture (TRYON, 2015; SARMENTO, 2018; FAGUNDES; ANEAS, 2021) with the purpose of understanding their historical articulations and their contemporary reconfigurations. Our methodology is anchored in the feminist film analysis (DE LAURETIS, 1987; GOMES BARBOSA, 2017; GOMES BARBOSA; MENDONÇA, 2021) and in the analysis of audiovisual materiality (COUTINHO, 2018; LEMOS, 2021). Together, these methodological procedures allowed us to observe the formal aspects of the narrative and how they are linked to the performative perspective of gender construction. In this research, we highlight the interest of this universe in incorporating, from the matrix of gender intelligibility, emancipatory and collective references, at the same time that it is interested in narrating an individual feminism that sanctifies the reproductive capacity of cisgender women. We show that, from Anne with E, there is an audiovisual commitment to capturing gender performativities in their ambivalences, building them from linguistic limitations and normative fields of power, such as traditional binary thinking. We identified six main articulations of gender performativities in the series, which are directed to discussions about beauty, affective relationships, intersectional aspects, bildungsroman, feminism and emancipation and political protagonism. We also present, in this dissertation, how the centrality of consumption that governs Netflix's policies can impact the articulation of these gender performativities.